Chemical Profile and Biological Activity of Cherimoya (Annona cherimola Mill.) and Atemoya (Annona atemoya) Leaves - Giuseppe Mannino; Carla Gentile; Alessandra Porcu; Chiara Agliassa; Fabio Caradonna; Cinzia Margherita Bertea (Molecules, 2020)
Annona cherimola (Cherimoya) and Annona atemoya (Atemoya) are tropical plants known for their edible fruit. Scientific data suggest that their leaves, used in traditional medicine in the form of teas or infusions without evidence of toxicity, contain several bioactive compounds. However, only Annona muricata among all the Annona species is currently used in the nutraceutical field, and its dried leaves are marketed for tea preparation. In this work, we explored the nutraceutical potential of Atemoya and Cherimoya leaves, by evaluating their chemical profile and functional properties. Phytochemical analyses showed large amounts of phenolic compounds, in particular proanthocyanidins, and identified 18 compounds, either flavonoids or alkaloids. Concerning biological activity, we found antioxidative properties correlated with polyphenols, and antiproliferative activity against HeLa and HepG2 cell lines correlated with alkaloids. The obtained results demonstrate the potential use of Annona cherimola leaves for the preparation of dietary supplements aimed to promote the physiological redox balance. Moreover, the varietal comparison suggests that two commercial cultivars (Campas and White) and the local Torre 1, better suit this purpose. On the other hand, among the studied cultivars, Campas and Torre 1 are also the richest in alkaloids and, in consideration of the anti-proliferative properties of their extracts, dietary supplements based on these cultivars might also have chemo-preventive effects.